2019
DOI: 10.1016/j.heliyon.2019.e01585
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for use of Acorus calamus (asarone) for cancer chemoprevention

Abstract: Cancer is one of the major non-communicable diseases posing substantial challenges in both developing and developed countries. The options available for treatment of different cancer are associated with various limitations, including severe toxicity, drug resistance, poor outcomes and a high risk of relapse. Hence, an increased attention and necessity for screening of various phytochemicals from natural sources for superior and safer alternative has been ongoing for several decades. In recent years, phytochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 47 publications
0
23
0
2
Order By: Relevance
“…There is a body of evidence suggesting that metformin reduces tumor growth directly through the inhibition of energy metabolism and by regulation of both AMPKdependent and independent signaling pathways [17][18][19][20]. On the other hand, alpha (α)-and beta (β)-asarone, the two major active constituents in volatile oils of Acorus calamus, showed anti-cancer effects in various cancer cell lines [21,22]. Our previous study showed that asarone treatment attenuated the progression of HCC in diabetic conditions in a similar manner to that achieved by metformin [23].…”
Section: Introductionmentioning
confidence: 99%
“…There is a body of evidence suggesting that metformin reduces tumor growth directly through the inhibition of energy metabolism and by regulation of both AMPKdependent and independent signaling pathways [17][18][19][20]. On the other hand, alpha (α)-and beta (β)-asarone, the two major active constituents in volatile oils of Acorus calamus, showed anti-cancer effects in various cancer cell lines [21,22]. Our previous study showed that asarone treatment attenuated the progression of HCC in diabetic conditions in a similar manner to that achieved by metformin [23].…”
Section: Introductionmentioning
confidence: 99%
“…The oil contains varying concentrations of αasarone, β-asarone, γ-asarone, calamenenolcalamene, calameone, camphene, α-pinene, β-pinene, p-cymene, eugenyl acetate, eugenol, isoeugenol, methyl isoeugenol, azulene, calamol, eugenol methyl ether, dipentene, methyl eugenol, asaronaldehyde, terpinolene, camphor, 1,8-cineole, αcaryophyllene and hydrocarbons (24)(25)(26). The oil also contains fatty acids such as palmitic acid and its ester, heptylic acid, an ester of butyric acid (27).…”
Section: Pluricaulis Contains D-glucose Maltose Rhamnosementioning
confidence: 99%
“…Among these, alpha-asarone and beta-asarone were the two main compounds isolated [ 52 ]. Various studies have reported A. calamus to be comprising of anti-ulcer, anti-inflammatory, anti-allergic, anti-microbial, anti-fungal, anti-oxidant, anti-diabetic, anti-cancer, neuroprotective, cardioprotective, insecticidal, and pesticidal properties [ 53 ]. α -asarone and β-asrone are the major phytocomponent found in leaves, very well known for their memory enhancement, behavioral modifications, learning performance, and antioxidant potentials [ 54 ].…”
Section: Herbal Treatment To Cure Alzheimer’s Diseasementioning
confidence: 99%